The effect of foliar applied zinc and copper on young oil palm (Elaeis guineensis Jacq.) - Ahmad Fuad, Nur Nadia Farlina (2015)
Malaysia is the second largest oil palm producer after Indonesia. In 2013, the hectarage of oil palm plantation was 5.3 million hectares. This shows an increase of about 13% compared to 4.69 million hectares in 2009. Malaysian soils consist mainly of Ultisols and Oxisols which are highly weathered. These soils are usually acidic with pH of less than 5. There are major nutritional constraints for oil palm production. Few oil palm plantations on upland soils apply micronutrients such as Zn and Cu. The objective of this study is to determine the effects of Zinc and Copper applied as foliar application and to investigate the difference in amount absorbed between Sulphate and EDTA source for Zinc and Copper on immature oil palm. The hypothesis for this study is that the application of foliar fertilizer as EDTA form will be a better source than Sulphate form in the uptake of Zinc and Copper. For the soil, it does not show any difference. The leaf and soil samples were taken at United Malacca Berhad, Machap Estate, Melaka. The experimental design was Complete Randomized Design (CRD). There were 7 treatments and each treatment will have 3 replications. The treatments were NPKMgB,NPKMgB + CuSO4, NPKMgB + CuEDTA, NPKMgB + ZnSO4, NPKMgB + ZnEDTA, NPKMgB + ZnSO4 + CuSO4 and NPKMgB + ZnEDTA + CuEDTA. The laboratory analysis was conducted in Faculty of Agriculture at Department of Land Management. The analysis involve were soil and plant tissue analysis. For the soil analysis, the total N, available P, CEC, pH , organic carbon and double acid methods for total Zn,Cu, Fe and Mn were determined. For the plant tissue, total N and dry ashing methods were analyzed. The application of Zn and Cu in the form of sulphate and EDTA did not show any significant effect on zinc and copper concentration on leaves. There was no difference between control and other treatments.